The Benefit and Cost of Winner Picking: Redistribution Vs Incentives - Axel Gautier; Florian Heider (University of Bonn, Bonn Graduate School of Economics (BGSE), 2002)
The Benefit and Cost of Winner Picking: Redistribution Vs Incentives |AB| A multi-divisional firm can engage in "winner-picking" to redistribute scarce funds efficiently across divisions. But there is a conflict between rewarding winners (investing) and producing resources internally to reward winners (incentives). Managers in winning divisions are tempted to free-ride on resources produced by managers in loosing divisions whose incentives to produce resources, anticipating their loss, are also weakened. Corporate headquarter's investment and incentive policy are therefore inextricably linked and have to be treated as jointly endogenous. The analysis links corporate strategy, compensation and the value of diversification to the characteristics of multi-divisional firms.
Keywords: G34; G31; L23; 330; Conglomerate; Internal capital market; Konglomerat; Profit Center; Betriebliche Budgetierung; Leistungsanreiz; Moral Hazard; Wettbewerbsstrategie; Diversifikation; Kosten-Nutzen-Analyse; Theorie